Revisiting the relationship between the principle of benevolence and beneficence - A. A. Stenishcheva (Вестник Майкопского государственного технологического университета)
The relevance of the research is substantiated by the fact that the principles of the educational process are almost always interconnected in their essence. However, usually a separate principle is taken as a basis, while establishing the relationship between the principles of benevolence and beneficence contributes to a much deeper understanding of the dialectics of educational interactions.The problem statement: without a sense of benevolence and beneficence, learners are less likely to be interested in thinking and acting in ways that meet the needs of others.The goal of the research is to analyze contemporary literature to identify the relationship between the principle of benevolence and beneficence, which should encourage young people to know about the lives of other people and specific circumstances.The object of research is the principles of benevolence and beneficence as humanitarian prerequisites for the moral process, and the subject is the education of the individual on this basis.The research method is conceptual analysis. A detailed examination of the presented concepts, which forms a clear idea of their essence and content, deserves special attention in this work.The conclusions: in order to understand what exactly contributes to the formation of a basis for familiarity with different points of view and worldviews, as well as with the structural causes of social problems and the potential consequences of actions taken to solve them, aspects for the emergence of these principles were considered. Also, during a detailed study of materials devoted to this issue, the principle of justice and charity has been discovered and described in the context of the connection between benevolence and beneficence. It has been noted that the use of the principle of benevolence and beneficence, considering age characteristics, can become one of the foundations in determining the mechanisms for implementing the continuity of teacher education.The results of the study can be used not only in training teachers, but can also be useful for specialists in the field of psychology, culture, etc.